Odpowiedzi

  • Użytkownik Zadane
2009-12-14T13:46:06+01:00
Zad. 1

a0=3
a1=33=3*10+a0
a2=3*100+a1
an=3*10^n+an-1

suma trzech elementów:
a0+a1+a2=a0+ 3*10+a0 + 3*100+a1 = a0+ 3*10+a0 + 3*100+3*10+a0=
= 3*a0+3*(100+2*10)

stąd można wyprowadzić wzór ogólny:

Sn= n*a0+3*(10^(n-1)+2*10^(n-2)+...+(n-1)*10^1)

Zad.2

a0=1/6
a1=1/12=1/2*a0
a2=1/24=1/2*a1
itd

suma 3 elementów

a0+a1+a2=a0+ 1/2*a0 + 1/2*a1=a0+ 1/2*a0 + 1/2*1/2*a0 =
=a0(1+1/2+(1/2)^2)

stąd wzór ogólny

Sn=a0(1+1/2+(1/2)^2+...+(1/2)^(n-1))

operacja ^ to operacja potęgowania
2 3 2